Analisis kualitas gula merah tebu hasil olahan tradisional dari Desa Pakak Kecamatan Kayan Hilir Kabupaten Sintang - Farah Diba; Ricky Chandra; Dina Setyawati; Hikma Yanti; Yeni Mariani (AGROINTEK, 2026)
Sugar cane is a fairly abundant agricultural product, often used as a raw  material for making granulated sugar, brown sugarcane, and liquid sugar. This research aims to describe the process of making brown sugar cane which is made traditionally by the people of Pakak Village, Kayan Hilir District, Sintang Regency, and analyze the quality of brown sugar cane. Making brown sugar cane was conducted by in-depth interviews with the people in Pakak village. The quality of brown sugar cane was carried out at the Chemistry Forest Product Laboratory, Faculty of Forestry, Tanjungpura University and Baristan Laboratory. The quality analysis included color, taste, texture, borax content, water content, ash content, water insoluble materials, sucrose and reducing sugar content. The testing procedure based on SNI 01-6237-2000. The result of in-depth interview found the process of making brown sugar cane sugar using traditional tools, and cooking it in a pan on a stove for 3-4 hours then put in the brown sugar cane font. The results of color brown sugar cane used pentone color resulted two types of color, namely Solid and CMYK colors, in categorized brown colour. The texture was a slightly soft  and hard texture, the brown sugar cane has no borax content. The water content of brown sugar cane ranges from 13,6%-16%, the ash content ranges from 2,5%-9%, the water insoluble material ranges 1,62%-3,04% , the sugar reduction ranges from 14.83%-19.92 %, and sucrose ranges from 57% - 70.9%. The quality of brown sugar cane from Pakak Village Kayan Hilir District Sintang Regency fulfill the standard of SNI 01-6237-2000 and safety foods because no borax content was found in the brown sugar cane.